Schoolchildren’s Compensatory Strategies and Skills in Relation to Attention and Executive Function App Training - Rossignoli-Palomeque, Teresa; Quiros-Godoy, María; Perez-Hernandez, Elena; González-Marqués, Javier (Frontiers in Psychology, 2019)
Background Given the importance of attention and executive functions (EF) in children’s behavior, programs aimed at improving these processes are of special interest. Nexxo-training combines the use of the Nexxo touchscreen application (inhibition and vigilance tasks) with procedural metacognitive strategies (imparted by an instructor) for all the individuals using the app, regardless of their level of ability, plus compensatory strategies based on individual child performance. This study presents an analysis of the compensatory strategies that schoolchildren (aged 6–8 years old) receive when experiencing difficulties with EF tasks, in addition to an analysis of the developmental factors and cognitive skills that may modulate EF task performance. Methods For this study, we use data from a previous randomized active-controlled study (under review), in which forty-six typically developing children aged between 6 and 8 years old (24 girls/22 boys) were enrolled in the training group. The selected children were in the 1st grade (n = 28, x¯ = 78.32 ± 4.037 months) and 3rd grade of primary education (n = 18, x¯ = 102.11 ± 3.445). We collected data on EF training performance, compensatory strategies needed and neuropsychological assessments. Results A total of 80.43% participants required some form of compensatory strategy during training. Regarding required compensatory strategies, those who had lower scores in EF training needed more compensatory strategies, in particular, instructional comprehension (r = −0.561, p < 0.001 for inhibition-tasks; r = −0.342, p < 0.001 for vigilance-tasks). Concerning developmental factors, age significantly predicted better performance in both EF tasks (β = 0.613, p < 0.001 for inhibition; β = 0.706, p < 0.001 for attention). As regards task performance, those with better performance in inhibition tasks also had better performance in vigilance tasks (r = 0.72, p < 0.001). Finally, regarding cognitive skills, participants with higher performance in fluid intelligence (Q1, n = 12) had higher scores (U = 14.5, p < 0.05) than the group with the lowest performance (Q4, n = 11) in vigilance. Conclusion As previous literature suggests, inhibition is one of the core processes of EF. Therefore, we should focus training on the core EF processes. Inhibition and vigilance are closely related processes. In terms of the use of compensatory strategies, these are more needed for participants with lower levels of performance in inhibition or vigilance. Regarding strategy analysis, instructional comprehension and self-instruction (goal setting and planning) seem to be the most useful strategies for those with difficulties in inhibitory and vigilance task performance. Regarding development, as expected, age moderates task performance in inhibition and attention. Finally, cognitive skills, such as fluid intelligence and cognitive flexibility, predicted better results in attention. EF training using not only an app, but also compensatory strategies based on user performance, is a new research direction offering more opportunities to generalize EF training in everyday life.